Cinematic Hamlet : the films of Olivier, Zeffirelli, Branagh, and Almereyda - Cook, Patrick J., 1951- (Ohio University Press, 2011)
Hamlet has inspired four outstanding film adaptations that continue to delighta wide and varied audience and to offer provocative new interpretationsof Shakespeare's most popular play. Cinematic Hamlet contains the first scene-by-scene analysis of the methods used by Laurence Olivier, Franco Zeffirelli, Kenneth Branagh, and Michael Almereyda to translate Hamlet into highly distinctive and remarkably effective films. Applying recent developments in neuroscience and psychology, Patrick J. Cook argues that film is a medium deploying an abundance of devices whose task it is to direct attention aw.